Evaluation of Mango (Mangifera indica L.) Cultivars for Flowering, Fruiting and Yield Attributes - Hada, T. S.; Singh, A. K. (International Journal of Bio-resource and Stress Management, 2017)
A field experiment was conducted to investigate the flowering, fruiting and yield attributes of some mango cultivars for the years 2014−15 and 2015−16. Outcome of the present research work revealed that the date of panicle emergence in different mango cultivars varied in both the years. It was observed that the panicle emergence was earliest in Gulabkhas and late in Fazli in both the years. Chausa produced maximum panicle length (35.19 cm) and breadth (24.76 cm). In the year 2014−15, earliest flowering was noted in Gulabkhas (Feb 17−Feb 26) and in the year 2015−16, earliest flowering was observed in Bombai (Feb 20−Feb 28) while, flowering was very late in Sepiya for both the years. Maximum number of flowers was observed in Langra (1839.13) while, minimum number of flowers was recorded in Amrapali (954.75). The duration of flowering varied from 22.50−36.00 days in different mango cultivars. Maximum value in terms of days was observed with Sepiya (39 days) while it was minimum (22.50 days) in case of Alphonso. The data revealed that date of fruit set ranged from 11th−8th April. Earliest fruit setting was observed in Bombai (12th−16th March) during the year 2014−15 while, earliest fruit setting was noted in Gulabkhas (10th March−16th March) during the year 2015−16. Highest number of fruit set panicle-1 was recorded in Langra (137.75) while, maximum fruit set per cent was noted in Bombai (41.07%). Minimum days for maturity was taken by Gulabkhas (90.17 days). Maximum yield (501.00 kg tree-1) was recorded in Langra.